2020
DOI: 10.3390/ijms21062042
|View full text |Cite
|
Sign up to set email alerts
|

Abscisic Acid and Jasmonate Metabolisms Are Jointly Regulated During Senescence in Roots and Leaves of Populus trichocarpa

Abstract: Plant senescence is a highly regulated process that allows nutrients to be mobilized from dying tissues to other organs. Despite that senescence has been extensively studied in leaves, the senescence of ephemeral organs located underground is still poorly understood, especially in the context of phytohormone engagement. The present study focused on filling this knowledge gap by examining the roles of abscisic acid (ABA) and jasmonate in the regulation of senescence of fine, absorptive roots and leaves of Popul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 98 publications
(137 reference statements)
0
6
0
Order By: Relevance
“…In our research, the levels of ABA, JA, and SA increased under S deficiency, while the application of Si decreased their level. These hormones are involved in plant response to mineral deficiencies and regulate the senescence process in plants [65,[76][77][78]. The lower level of phytohormones induced by Si nutrition in this study can be associated with the expression of S transporters.…”
Section: Si Regulates Source To Sink Metabolic Homeostasis and Maintamentioning
confidence: 63%
“…In our research, the levels of ABA, JA, and SA increased under S deficiency, while the application of Si decreased their level. These hormones are involved in plant response to mineral deficiencies and regulate the senescence process in plants [65,[76][77][78]. The lower level of phytohormones induced by Si nutrition in this study can be associated with the expression of S transporters.…”
Section: Si Regulates Source To Sink Metabolic Homeostasis and Maintamentioning
confidence: 63%
“…The plant hormone JA and its derivatives are involved in various aspects of plant growth, such as biotic, abiotic stresses, and development (Chen et al., 2020; Fugate et al., 2018; Hu et al., 2017; Seo et al., 1999; Suzuki et al., 2021; Wojciechowska et al., 2020). Recent studies showed that JA is also involved in SCW formation (Behr et al., 2019; Pauwels et al., 2008; Sehr et al., 2010).…”
Section: Discussionmentioning
confidence: 99%
“…ABA induces a delay in cell elongation by inhibiting cytokinin signaling, consequently root architecture is altered, and root growth is retarded (Wang et al 2019). Root senescence was controlled by the regulation of jasmonate and ABA (Wojciechowska et al 2020). ABA, salicylic acid and methyl jasmonate increased the sulphoraphene and glucosinolate accumulation in taproots (Chen et al 2019).…”
Section: Modulation Of Root Architecturementioning
confidence: 99%